Representative public authorities and subsurface users enterprises in the industrial cities of the Ural region - Vitkovskaya, T.B. (Perm Federal Research Centre Journal, 2021)
This paper looks into the participation of enterprises - subsurface users in the political life of the Ural industrial cities. The involvement of enterprises - subsoil users in the urban social and political life is due to their close connection with the territory, subsoil and urban infrastructure. Participation in the activities of local government bodies gives subsurface users the access to policy implementation in the city. Participation of subsurface users in the work of local legislatures involves them in defining issues that are included in the city agenda and in decision-making process that affects the local community and territory.